In Vitro and In Vivo Anti-infective Potential of Thymol Against Early Childhood Caries Causing Dual Species Candida albicans and Streptococcus mutans - Priya, Arumugam; Selvaraj, Anthonymuthu; Divya, Dass; Karthik Raja, Ramalingam; Pandian, Shunmugiah Karutha (Frontiers in Pharmacology, 2021)
Early childhood carries (ECC), a severe form of caries due to cross kingdom interaction of Candida albicans and Streptococcus mutans is a serious childhood dental disease that affects majority of the children with poor background. The present study investigated antiinfective potential of thymol against C. albicans and S. mutans dual species for the management of ECC. Thymol, a plant derivative of monoterpene group has been well known for its numerous biological activities. Thymol at 300 µg/mL concentration completely arrested growth and proliferation of dual species of C. albicans and S. mutans. Rapid killing efficacy of pathogens, within a span of 2 minutes was observed in time kill assay. In addition, at sub-inhibitory concentrations, thymol effectively diminished the biofilm formation and virulence of both C. albicans and S. mutans such as yeast to hyphal transition, hyphal to yeast transition, filamentation and acidogenicity and acidurity, respectively in single and dual species state. qPCR analysis was consistent with virulence assays Also, through the invertebrate model system Galleria mellonella, in vivo toxicity and efficacy of the phytocompound was assessed and it was found that no significant toxic effect was observed. Moreover, thymol was found to be proficient in diminishing the infection under single and dual state in in vivo condition. Overall, the results from the present study illustrates the antiinfective potential of thymol against the ECC causing dual species, C. albicans and S. mutans and the applicability of thymol in medicated dentifrice formulation.